Reversed double-beam photoacoustic spectroscopy of metal-oxide powders for estimation of their energy-resolved distribution of electron traps and electronic-band structure. (20th February 2018) - Nitta, Akio; Takashima, Mai; Murakami, Naoya; Takase, Mai; Ohtani, Bunsho
Abstract: A novel instrumental methodology, reversed double-beam photoacoustic spectroscopy (RDB-PAS), was developed for measuring the energy-resolved distribution of electron traps (ERDT) of metal-oxide powders. In the RDB-PAS measurement, electrons in the valence band of a powder sample are directly excited to electron traps (ETs) and accumulated in the ETs from the deeper (anodic) side to the shallower (cathodic) side by wavelength-scanned continuous light, and the increase in photoabsorption of electron-filled ETs is measured by modulated light at a fixed wavelength by PAS. It was shown that ERDT/CBB (conduction-band bottom) patterns measured by RDB-PAS can be used for not only identification and detailed characterization of a wide range of metal-oxide powder samples but also estimation of difference in apparent valence-band top (VBT) position. Graphical abstract: Highlights: Energy-resolved distribution of electron traps (ERDT) in metal-oxide powders was measured. Reversed double-beam photoacoustic spectroscopy (RDB-PAS) was developed for ERDT analysis. ERDT analysis enabled estimation of valence-band top energy of titania samples.